Updates on Corticosteroids - Radenkovic, Miroslav (IntechOpen, 2023)
Corticosteroids are frequently prescribed drugs. Systemic corticosteroids possess potent anti-inflammatory, immunomodulatory, and certain antineoplastic properties, thus being pivotal in the treatment of autoimmune diseases, allergic reactions, arthritic diseases, asthma exacerbations, neurological disorders, septic shock, and selected malignancies. Moreover, topical use of corticosteroids is essential in the treatment of dermatological and ophthalmological conditions as well as chronic asthma. Finally, administration of antenatal and postnatal corticosteroids is one of the most important features of modern obstetrics and neonatology. As such, this book provides a comprehensive overview of corticosteroids, including their pharmacological properties and clinical use, and addresses uncertainness in their appropriate prescribing.